Penyuluhan dan Pelatihan Pembuatan UMB (Urea Molasses Block) Pada Peternak Sapi Potong di Desa Blengorwetan, Kecamatan Ambal, Kabupaten Kebumen - Vian Dwi Chalisty; Eko Priyono; Ibnu Soleh; Nuryani Nuryani; Siti Aminah; Rinjani Rinjani; Siti Nur Aini; Siti Maskuroh; Lili Kusmiati; Holisoh Istinganatun (Abdibaraya: Jurnal Pengabdian Masyarakat, 2022)
Blengorwetan Village, Ambal District, Kebumen Regency is an area with the potential for developing Kebumen PO cattle farms, but has problems in terms of fulfilling animal feed nutrients. The majority of farmers provide feed in the form of dry rice straw, which is low in protein, vitamins, and minerals, and high in crude fiber. Based on these problems, this community service activity aims to provide counseling and training on the manufacture of Urea Molasses Block (UMB) to farmers. Urea Molasses Block (UMB) is an animal feed supplement that serves to improve the nutritional value of animal feed; digestion and digestibility of animal feed substances will be more efficient and improved; consumption of ruminant feed will increase, and avoid vitamin and mineral deficiencies. The methods used include field surveys, discussions with village officials, socialization to increase the knowledge of farmers about UMB, and training in making UMB which is followed in a participatory manner by the community. Trials of giving UMB to livestock by the community show UMB is favored by livestock and can increase animal feed consumption. Based on the activities that have been carried out, it can be concluded several things, namely (1) the training on making UMB has been successfully implemented with indicators of understanding and skills of cattle farmers increasing regarding UMB products and how to manufacture them, (2) UMB products produced are of sufficient quality and favored by livestock. , (3) further breeders wish to make UMB products independently for consumption by their own livestock, with the hope of increasing livestock productivity. Keywords: Urea Molasses Block, Livestock, Feed Supplement